The Effectiveness of E-Comic Media in Science Learning to Enhance Students’ Learning Interest: Insights from Ayat Kauniyah - Ayu Yudianti, I Gusti; Hasanah, Tita; Rusydi, Lina Najwatur (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to examine the effectiveness of e-comic media in enhancing students’ learning interest in science learning, while also offering insights from ayat kauniyah (Qur’anic signs in nature) as a complementary perspective in Islamic education. The use of e-comics in science learning is not only intended to increase motivation and engagement, but also to encourage students to observe and reflect on the magnificence of Allah’s creation through natural phenomena. The research employed a quantitative approach using a quasi-experimental design with a Post-test Only Control Group, involving 66 fifth-grade students selected purposively. Learning-interest data were collected through validated questionnaires, and hypothesis testing was conducted using the Independent Sample T-test. The results show that the experimental group using e-comic media achieved a higher post-test mean score (75.4) compared to the control group (65.8). Statistical analysis using SPSS 26 for Windows revealed a significance value of 0.00 < 0.01, indicating a strong effect of e-comic media on students’ learning interest. These findings suggest that e-comic media is effective in improving students’ learning interest in science education and, when interpreted through the lens of ayat kauniyah, can support the cultivation of spiritual reflection, gratitude, and awareness of Allah’s signs within the broader aims of Islamic pedagogy.